Pathophysiology of SARS-CoV-2 in Lung of Diabetic Patients - Oliveira, Tales Lyra; Melo, Igor Santana; Cardoso-Sousa, Léia; Santos, Igor Andrade; El Zoghbi, Mohamad Bassim; Shimoura, Caroline Gusson; Georjutti, Renata Pereira; Castro, Olagide Wagner; Goulart, Luiz Ricardo; Jardim, Ana Carolina Gomes; Cunha, Thúlio Marquez; Sabino-Silva, Robinson (Frontiers in Physiology, 2020)
Coronavirus disease (COVID-19) is an infectious disease caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2). Its impact on patients with comorbidities is clearly related to fatality cases, and diabetes has been linked to one of the most important causes of severity and mortality in SARS-CoV-2 infected patients. Substantial research progress has been made on COVID-19 therapeutics; however effective treatments remain unsatisfactory. This unmet clinical need is robustly associated with the complexity of pathophysiological mechanisms described for the COVID-19. Several key lung pathophysiological mechanisms promoted by SARS-CoV-2 have driven the response in normoglycemic and hyperglycaemic subjects. There is sufficient evidence that glucose metabolism pathways in the lung are closely tied to bacterial proliferation, inflammation and oxidative stress, which lead to severe clinical outcomes. It is also likely that SARS-CoV-2 proliferation is affected by glucose metabolism of type I and type II cells. This review summarizes the current understanding of pathophysiology of SARS-CoV-2 in the lung of diabetic patients and highlights the changes in clinical outcomes of COVID-19 in normoglycemic and hyperglycaemic conditions.